Modular memristor circuits for Pavlov associative memory with scalability - Xiaoyuan Wang; Zhenyu Ge; Mingyang Wu; Xinrui Zhang; Zhonghai Zhang; Xiaolu Lucia Li; Herbert Ho-Ching Iu; Sung-Mo Kang (Cognitive Neurodynamics, 2026)

Subtropical climate and intraday temperature variability: Mental health risks and modifying roles of demographic and seasonal factors in Texas - Yue Zhang; Kaili Zhang; Yizhen Ding; Chia-Ching Wu; Dongying Li (Sustainable Cities and Society, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

Integration Mechanisms and Performance in Port–Hinterland Supply Chains: A Systematic Review - Hao Zhang; Mark Ching-Pong Poo; Yui-yip Lau; Shiqi Fan (Journal of Marine Science and Engineering, 2026)
Port–hinterland links are a major driver of performance in maritime supply chains, affecting landed cost, service reliability and environmental outcomes. Yet research on ports and inland freight remains fragmented across transport geography, logistics, operations research and governance studies. This review consolidates evidence on how physical, operational, governance and digital integration levers shape supply chain outcomes at the port–hinterland interface. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-informed protocol was applied to Web of Science Core Collection records retrieved with a title-level port–hinterland query, last updated on 23 November 2025. The qualitative synthesis covers 90 peer-reviewed studies published from 2008 to 2026. Four eligible records (IN22, IN30, IN54 and IN83) could not be retrieved as full texts and are excluded from the qualitative synthesis; their metadata are retained only in the 94-record bibliometric keyword layer. The review traces the evolution from spatial and administrative views of hinterlands toward functional, network-based and actor-centred perspectives, and synthesises seven streams: delimitation and port choice, corridor competition, dry ports and extended gates, coordination and governance, multimodal operations, digitalisation, and sustainability and resilience. It proposes a four-layer conceptual framework linking infrastructure, services, governance and information integration to cost, reliability, capacity, emissions and resilience. The evidence base remains dominated by model-based studies that offer limited causal identification, supporting a focused agenda for more empirically grounded port–hinterland supply chain research.

Human pegivirus co-infection in SARS-CoV-2: Prevalence and clinical associations - Mathieu Garand; Ching Ching Zhang; Grace Guo; Pranav Kirti; Jack T. Stapleton; Pirooz Eghtesady (Next Research, 2026)

Subject-specific whole-lung CFPD coupled with PBPK/PD to predict inhaled bronchodilator response in asthmatic and healthy subjects - Prathish K. Rajaraman; Xuan Zhang; Alejandro P. Comellas; Eric A. Hoffman; Ching-Long Lin (Journal of Aerosol Science, 2026)

Programmable viscoelastic hydrogel enables factor-free adipogenesis of MSCs through mechanotransduction - Tianyue Li; Yanwen Wang; Ziyuan Li; Poh-Ching Tan; Chenghuizi Hu; Jiajun Jin; Shuang-Bai Zhou; Qing-Feng Li; Junji Zhang (Chemical Engineering Journal, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Genomic epidemiology and antimicrobial resistance of nontyphoidal Salmonella in retail meats in Hong Kong: A comprehensive surveillance study using whole-genome sequencing - Ivan Tak-Fai Wong; Iain Chi-Fung Ng; Dorothy Hong-Ting Cheung; Wing-Yin Tam; Choi-Ying Wong; Sharon Ka-Yee Fung; Ho-Ching Tong; Shue-Kei Chan; Tsz-Ying Wu; Elaine Yin-Ting Yeung; Jiaying Zhang; Franklin Wang-Ngai Chow; et al. (Food Research International, 2026)

Reef fish assemblages show limited response to giant clam density and restocking - Nathan W. Price; Yan-Zhen Meng; Wen-Yuan Zhang; Jinn-Shing Weng; Ching-Min Yang; Kao-Sung Chen; Joseph Heard; Wei-Chen Tung; Yu-De Pei; Colin Kuo-Chang Wen (Regional Studies in Marine Science, 2026)

Post‐Drought Vegetation Shifts Lead to Divergent Carbon, Water and Energy Responses in a Savanna Ecosystem of Southwest China - Palingamoorthy Gnanamoorthy; Junbin Zhao; Yajun Chen; Linjie Jiao; Boonsiri Sawasdchai; Zhang Jing; Abhishek Chakraborty; Pramit Kumar Deb Burman; Sung‐Ching Lee; Thomas A. M. Pugh; Yiping Zhang; Qinghai Song (Ecology Letters, 2026)
Increasing drought frequency and intensity affect biophysical functions of natural ecosystems. In tropical semi‐arid savannas, while immediate drought effects are well‐studied, the drought legacy effects on vegetation composition and associated ecosystem functions remain unclear. We used data of vegetation composition, net ecosystem CO 2 exchange, surface albedo and evapotranspiration (ET) in 2017–2022 from a savanna ecosystem, Southwest China, to investigate the legacy effect of an extreme drought event that occurred in 2019. Vegetation declined continuously for 3 post‐drought years. While tree numbers declined by 12%, shrub numbers dropped by 50% compared with pre‐drought levels, shifting vegetation dominance toward trees. This structural change caused sustained reductions in albedo and ET, which remained below pre‐drought levels, despite gross primary production recovering in the years immediately post‐drought. Vegetation shifts disproportionately impact ecosystem functions, with energy and water fluxes exhibiting greater vulnerability and potentially enhancing regional warming as droughts increase in Asian savannas.

Seawater-conditioned cement as a viable substrate for coral larval settlement - Elizaldy Acebu Maboloc; Jason Hon-Yin Szeto; Ken Chue-Ho Yuen; Shirley Chun-Ching Wong; Juan Carlos Astudillo; Lin Cai; Lucen Hao; Shipeng Zhang; Apple Pui-Yi Chui; James Kar-Hei Fang (Regional Studies in Marine Science, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Oil-based micro-sized extraction system designed from O/W Pickering emulsion template for highly efficient nanoplastics removal in the gastrointestinal tract - Xiao Fu; Chi Zhang; Xiao Tong Lu; Fang Xiao Guo; Xu Zhang; Huixia Zhou; Xin-Ai Guo; Xiaoyu Wang; Ching Yuan Hu; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2025)

A Review of Atmospheric Micro/Nanoplastics: Insights into Source and Fate for Modelling Studies - Fei Jiang; Chengze Gao; Arthur W. H. Chan; David O. Topping; Hongliang Zhang; Weijun Li; Hugh Coe; Xiaohong Liu; Joseph Ching; Zhonghua Zheng (Current Pollution Reports, 2025)
Purpose of Review Micro/nanoplastics (MNPs), as emerging pollutants, have attracted increasing attention due to their potential adverse effects on human health, ecosystems, and climate. The rapid, turbulent, and large-scale nature of atmospheric transport facilitates both horizontal and vertical movement of MNPs over long distances within a short time, largely independent of topographical constraints, thereby accelerating their global cycle and exacerbating their impacts. Despite growing interest, our understanding of the atmospheric lifecycle of MNPs remains limited. This review aims to synthesise recent advances in understanding the atmospheric lifecycle of MNPs, including their emission sources, long-range transport characteristics, and driving mechanisms. It also evaluates the key sources of uncertainty—particularly those related to emission flux estimates—and provides corresponding recommendations for future research. Recent Findings Current research on the atmospheric processes of MNPs primarily relies on a combination of observational data and numerical modelling. Two major uncertainties in atmospheric micro/nanoplastic (AMNP) emissions persist: the wide variability in marine emission estimates, which span four orders of magnitude, and the unresolved question of whether terrestrial or marine sources are the dominant contributors to AMNP emissions. Furthermore, this review highlights critical factors driving these uncertainties, including limited data availability, inconsistencies in observational methodologies, oversimplified simulations, and gaps in understanding atmospheric cycling mechanisms. Additionally, variations in the particle size ranges targeted by different observational and modelling studies hinder cross-comparisons and model evaluations, representing another important source of uncertainty. Summary AMNP research is constrained by multiple uncertainties that hinder a comprehensive understanding of their emissions, transport, and fate. To address these issues, we call for establishing a global network of standardised observations, improving sampling and simulation practices, and incorporating artificial intelligence. These strategies will enhance our understanding of the complete atmospheric cycle of MNPs, paving the way for more effective environmental management and better-informed policy decisions.

Electron transfer centers facilitate the degradation of antibiotics with an O-doped walnut shell biochar/periodate system - Xi Zhang; Alina Liyakat; Mohammadreza Kamali; Junwei Li; Bart Van der Bruggen; Ching-Hua Huang; Deirdre Cabooter; Raf Dewil (Chemical Engineering Journal, 2025)

Highly hydrovoltaic fabrics based on water evaporation drive for self-powered wearable - Xiaoyang Zhang; Xuefei Zhang; Hai-Tao Ren; Ting-Ting Li; Ching-Wen Lou (Chemical Engineering Journal, 2025)

Vacuum-assisted carbon molecular sieve membrane reactor for non-oxidative ethane dehydrogenation - Antara Bhowmick; H. Hasan Koybasi; Ching-En Ku; Genwei Chen; Sooyeon Hwang; Chen Zhang; Dionisios G. Vlachos; Dongxia Liu (Chemical Engineering Journal, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Interactions between environmental pollutants and gut microbiota: A review connecting the conventional heavy metals and the emerging microplastics - Xiaochen Chen; Zengdi Zhang; Yushiang Hsueh; Chunpeng Zhang; Jianying Yu; Junyu Zhu; Jia Niu; Naiyi Yin; Jianyu Zhang; Xiaoyu Cui; Xianhua Liu; Kaiqin Xu; et al. (Environmental Research, 2025)

Hijacking the hyaluronan assisted iron endocytosis to promote the ferroptosis in anticancer photodynamic therapy - Hong Deng; Jiayu Chen; Huimin Wang; Runmeng Liu; Yiyi Zhang; Hui Chang; Ching-Hsuan Tung; Weiqi Zhang (Carbohydrate Polymers, 2025)

Influence of antibody–drug conjugate cleavability, drug-to-antibody ratio, and free payload concentration on systemic toxicities: A systematic review and meta-analysis - Shou-Ching Tang; Carrie Wynn; Tran Le; Martin McCandless; Yunxi Zhang; Ritesh Patel; Nita Maihle; William Hillegass (Cancer and Metastasis Reviews, 2025)
While in theory antibody drug conjugates (ADCs) deliver high-dose chemotherapy directly to target cells, numerous side effects are observed in clinical practice. We sought to determine the effect of linker design (cleavable versus non-cleavable), drug-to-antibody ratio (DAR), and free payload concentration on systemic toxicity. Two systematic reviews were performed via PubMed search of clinical trials published between January 1998—July 2022. Eligible studies: (1) clinical trial for cancer therapy in adults, (2) ≥ 1 study arm included a single-agent ADC, (3) ADC used was commercially available/FDA-approved. Data was extracted and pooled using generalized linear mixed effects logistic models. 40 clinical trials involving 7,879 patients from 11 ADCs, including 9 ADCs with cleavable linkers ( N = 2,985) and 2 with non-cleavable linkers ( N = 4,894), were included. Significantly more composite adverse events (AEs) ≥ grade 3 occurred in patients in the cleavable linkers arm (47%) compared with the non-cleavable arm (34%). When adjusted for DAR, for grade ≥ 3 toxicities, non-cleavable linkers remained independently associated with lower toxicity for any AE ( p = 0.002). Higher DAR was significantly associated with higher probability of grade ≥ 3 toxicity for any AE. There was also a significant interaction between cleavability status and DAR for any AE ( p = 0.002). Finally, higher measured systemic free payload concentrations were significantly associated with higher DARs ( p = 0.043). Our results support the hypothesis that ADCs with cleavable linkers result in premature payload release, leading to increased systemic free payload concentrations and associated toxicities. This may help to inform future ADC design and rational clinical application.

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Solar-driven fast and selective extraction of lithium from seawater enabled by unidirectional photothermal conversion and confined crystallization with facile synthesis of nanoarray evaporator - Qihuan Liu; Zhen Yu; Yaoxin Zhang; Ke Mao; Weier Xiang; Shuai Guo; Ting Xiong; Swee Ching Tan (Chemical Engineering Journal, 2025)

Recent advancements and perspectives on processable natural biopolymers: Cellulose, chitosan, eggshell membrane, and silk fibroin - Xinhua Liang; Shuai Guo; Xiaoju Kuang; Xiaoqian Wan; Lu Liu; Fei Zhang; Gaoming Jiang; Honglian Cong; Haijun He; Swee Ching Tan (Science Bulletin, 2024)

Revisiting the synergistic oxidation of peracetic acid and permanganate(Ⅶ) towards micropollutants: The enhanced electron transfer mechanism of reactive manganese species - Yufei Shi; Shaoze Xiao; Yajie Qian; Ching-Hua Huang; Jiabin Chen; Nan Li; Tongcai Liu; Yalei Zhang; Xuefei Zhou (Water Research, 2024)

Beneath the lens: Exploring the impacts of underwater photographers in marine-based tourism - Anson T.H. Ma; Lewis T.O. Cheung; Ching Yee Lui; Alice S.Y. Chow; Ke Zhang; Theresa W.L. Lam; Lincoln Fok (Journal of Outdoor Recreation and Tourism, 2024)

On the low-velocity impact properties of CFRP/HAFRP interlayer hybrid fibre composite laminates - Ziwei Luo; Hongxu Wang; Ching-Tai Ng; Jiyang Fu; Zhifang Zhang; Caizheng Wang (Engineering Structures, 2024)

The Impact of Coal-Fired, Soot on China's Industrial Production and Total Factor Energy Efficiency - Zhihuan Xu; Taisheng Zhang; Lei Zhuang; Po-Feng Wu; Ching-Cheng Lu (Water, Air, & Soil Pollution, 2024)

Retraction Note: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the nexus between financial development and energy finance through demand- and supply-oriented physical disruption in crude oil - Fengsheng Chien; YunQian Zhang; Ching-Chi Hsu (Environmental Science and Pollution Research, 2024)

Retraction Note: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Experimental observation of exceptional bound states in a classical circuit network - Deyuan Zou; Tian Chen; Haiyu Meng; Yee Sin Ang; Xiangdong Zhang; Ching Hua Lee (Science Bulletin, 2024)

Risk Analysis of Pirate Attacks on Southeast Asian Ships Based on Bayesian Networks - Qiong Chen; Jinsheng Zhang; Jiaqi Gao; Yui-Yip Lau; Jieming Liu; Mark Ching-Pong Poo; Pengfei Zhang (Journal of Marine Science and Engineering, 2024)
As a bridge for international trade, maritime transportation security is crucial to the global economy. Southeast Asian waters have become a high-incidence area of global piracy attacks due to geographic location and complex security situations, posing a great threat to the development of the Maritime Silk Road. In this study, the factors affecting the risk of pirate attacks are analyzed in depth by using the Global Ship Piracy Attacks Report from the IMO Global Integrated Shipping Information System (GISIS) database (i.e., 2013–2022) in conjunction with a Bayesian Network (BN) model, and the Expectation Maximization algorithm is used to train the model parameters. The results show that piracy behaviors and the ship’s risk are the key factors affecting the risk of pirate attacks, and suggestions are made to reduce the risk of pirate attacks. This study develops a theoretical basis for preventing and controlling the risk of pirate attacks on ships, which helps maintain the safety of ship operations.

Improved resilience and proteostasis mediate longevity upon DAF-2 degradation in old age - Adrian Molière; Ji Young Cecilia Park; Anita Goyala; Elena M. Vayndorf; Bruce Zhang; Kuei Ching Hsiung; Yoonji Jung; Sujeong Kwon; Cyril Statzer; David Meyer; Richard Nguyen; Joseph Chadwick; et al. (GeroScience, 2024)
Little is known about the possibility of reversing age-related biological changes when they have already occurred. To explore this, we have characterized the effects of reducing insulin/IGF-1 signaling (IIS) during old age. Reduction of IIS throughout life slows age-related decline in diverse species, most strikingly in the nematode Caenorhabditis elegans . Here we show that even at advanced ages, auxin-induced degradation of DAF-2 in single tissues, including neurons and the intestine, is still able to markedly increase C. elegans lifespan. We describe how reversibility varies among senescent changes. While senescent pathologies that develop in mid-life were not reversed, there was a rejuvenation of the proteostasis network, manifesting as a restoration of the capacity to eliminate otherwise intractable protein aggregates that accumulate with age. Moreover, resistance to several stressors was restored. These results support several new conclusions. (1) Loss of resilience is not solely a consequence of pathologies that develop in earlier life. (2) Restoration of proteostasis and resilience by inhibiting IIS is a plausible cause of the increase in lifespan. And (3), most interestingly, some aspects of the age-related transition from resilience to frailty can be reversed to a certain extent. This raises the possibility that the effect of IIS and related pathways on resilience and frailty during aging in higher animals might possess some degree of reversibility.

Exploring environmental exposomes and the gut-brain nexus: Unveiling the impact of pesticide exposure - Shing Ching Khoo; Nan Zhang; Vijitra Luang-In; Meng Shien Goh; Christian Sonne; Nyuk Ling Ma (Environmental Research, 2024)

Editorial for special issue on additively manufactured structures - Nan Hu; Philippe Block; Josephine Carstensen; X. Shelly Zhang; Peng Feng; Ching Tai Ng (Engineering Structures, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Age and dietary restriction modulate mitochondrial quality in quadriceps femoris muscle of male mice - Ting-Rui Zhang; Chun-Hsien Chiang; Tzu-Chieh Hsu; Chih-Yun Wang; Ching-Yi Chen (Biogerontology, 2024)

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Longitudinal aortic strain, ventriculo-arterial coupling and fatty acid oxidation: novel insights into human cardiovascular aging - Hongzhou Zhang; Shuang Leng; Fei Gao; Jean-Paul Kovalik; Ru-San Tan; Hai Ning Wee; Kee Voon Chua; Jianhong Ching; Xiaodan Zhao; John Allen; Qinghua Wu; Tim Leiner; et al. (GeroScience, 2024)

Tribological characterisation of graphene hybrid nanolubricants in biofuel engines - Ching-Ming Lai; Heoy Geok How; Yeoh Jun Jie Jason; Yew Heng Teoh; Haseeb Yaqoob; Shengfu Zhang; Mohammad Rafe Hatshan; Farooq Sher (Fuel, 2024)

Medulla Tetrapanacis water extract alleviates inflammation and infection by regulating macrophage polarization through MAPK signaling pathway - Carsten Tsun-Ka Kwok; Franklin Wang-Ngai Chow; Karry Yuen-Ching Cheung; Xiao-Yi Zhang; Daniel Kam-Wah Mok; Yiu-Wa Kwan; Gabriel Hoi-Huen Chan; George Pak-Heng Leung; Ka-Wang Cheung; Simon Ming-Yuen Lee; Ning Wang; Jing-Jing Li; et al. (Inflammopharmacology, 2024)

Green cost performance measure of China’s thermal power industry: evidence from Chinese 30 provinces - Xiang Chen; Jiayu Zhang; Chih-Yu Yang; Ching-Cheng Lu; Jun Wang (Environment, Development and Sustainability, 2024)

Tree-ring eccentricity-based dating of landslide movements: Defining a new effective approach - Karel Šilhán; Karla Aurora De la Peña Guillén; Teodoro Carlón Allende; Ching-Ying Tsou; Yong Zhang (CATENA, 2024)

Performance and emission characteristics of double split injection biodiesel engine with intake air throttling - Ching-Ming Lai; Hau Kian Leong; Yew Heng Teoh; Heoy Geok How; Thanh Danh Le; Huu Tho Nguyen; Khaled Ali Al-Attab; Shengfu Zhang; Sabah Ansar; Farooq Sher (Journal of Cleaner Production, 2023)

Hydroxytyrosyl oleate is a promising safe additive to inhibit the oxidation of olive oil - Yan Yi Qi; Tian Gong; Peng Tao Zhao; Yong Jie Niu; Yong Yuan Hu; Ching Yuan Hu; Shuai Zhang; Yong Hong Meng (Food Control, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Chitosan-based antibacterial microspheres loaded multifunctional Janus composite membranes with unidirectional biofluid transport, antioxidant and pH-responsive monitoring - Ting-Ting Li; Li Sun; Ying Zhang; Bing-Chiuan Shiu; Hai-Tao Ren; Hao-Kai Peng; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Application of chitosan with different molecular weights in cartilage tissue engineering - Runjie Zhang; Shwu Jen Chang; Yanzhen Jing; LiYuan Wang; Ching-Jung Chen; Jen-Tsai Liu (Carbohydrate Polymers, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Preparation and study of bark-like MXene based high output power hydroelectric generator - Xiaoyang Zhang; Yanting Wang; Xuefei Zhang; Ching-Wen Lou; Jia-Horng Lin; Ting-Ting Li (Chemical Engineering Journal, 2023)

Unraveling effects of anti-aging drugs on C. elegans using liposomes - Aihan Zhang; Kuei Ching Hsiung; Carina C. Kern; Yuting Wang; Anna L. Girtle; Nuo Xu; David Gems (GeroScience, 2023)
Liposome-mediated delivery is a possible means to overcome several shortcomings with C. elegans as a model for identifying and testing drugs that retard aging. These include confounding interactions between drugs and the nematodes’ bacterial food source and failure of drugs to be taken up into nematode tissues. To explore this, we have tested liposome-mediated delivery of a range of fluorescent dyes and drugs in C. elegans . Liposome encapsulation led to enhanced effects on lifespan, requiring smaller quantities of compounds, and enhanced uptake of several dyes into the gut lumen. However, one dye (Texas red) did not cross into nematode tissues, showing that liposomes cannot ensure the uptake of all compounds. Of six compounds previously reported to extend lifespan (vitamin C, N -acetylcysteine, glutathione (GSH), trimethadione, thioflavin T (ThT), and rapamycin), this effect was reproduced for the latter four in a condition-dependent manner. For GSH and ThT, antibiotics abrogated life extension, implying a bacterially mediated effect. With GSH, this was attributable to reduced early death from pharyngeal infection and associated with alterations of mitochondrial morphology in a manner suggesting a possible innate immune training effect. By contrast, ThT itself exhibited antibiotic effects. For rapamycin, significant increases in lifespan were only seen when bacterial proliferation was prevented. These results document the utility and limitations of liposome-mediated drug delivery for C. elegans . They also illustrate how nematode-bacteria interactions can determine the effects of compounds on C. elegans lifespan in a variety of ways.

Transformation of dissolved organic matter during UV/peracetic acid treatment - Penghui Du; Wen Liu; Qiang Zhang; Peng Zhang; Chen He; Quan Shi; Ching-Hua Huang; Junjian Wang (Water Research, 2023)

Short-term Medication Effects on Brain Functional Activity and Network Architecture in First-Episode psychosis: a longitudinal fMRI study - Yajuan Zhang; Qiong Xiang; Chu-Chung Huang; Jiajia Zhao; Yuchen Liu; Ching-Po Lin; Dengtang Liu; Chun-Yi Zac Lo (Brain Imaging and Behavior, 2023)

A simulation-aided approach in examining the viability of passive daylighting techniques on inclined windows - Ya Hui Teo; Jun Hong Yap; Hui An; Nenggang Xie; Jie Chang; Simon Ching Man Yu; Wai Ching Poon; Limao Zhang; Kang Hao Cheong (Energy and Buildings, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Long-term dietary restriction ameliorates ageing-related renal fibrosis in male mice by normalizing mitochondrial functions and autophagy - Chun-Hsien Chiang; Sin-Jin Li; Ting-Rui Zhang; Ching-Yi Chen (Biogerontology, 2022)

Pharmaceutical nanoformulation strategies to spatiotemporally manipulate oxidative stress for improving cancer therapies — exemplified by polyunsaturated fatty acids and other ROS-modulating agents - Rui Xue Zhang; Franky Fuh-Ching Liu; Hoyin Lip; Junhong Liu; Qianrong Zhang; Xiao Yu Wu (Drug Delivery and Translational Research, 2022)

Correction to: Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Superiority of Adipose-derived CD34 + Cells over Adipose-derived Stem Cells in Promoting Ischemic Tissue Survival - Yan-Jun Liu; Tian-Yu Zhang; Poh-Ching Tan; Pei-Qi Zhang; Yun Xie; Qing-Feng Li; Shuang-Bai Zhou (Stem Cell Reviews and Reports, 2022)

RETRACTED ARTICLE: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the impact of green fiscal policies and energy poverty on energy efficiency - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Tai Duc Tran; Li Li (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2022)

Nutrient Accumulation and Environmental Risks of Biosolids and Different Fertilizers on Horticultural Plants - Min Pan; Pui Ching Yau; Kai Chun Lee; Hao Zhang; Vincent Lee; Cheuk Yi Lai; Ho Juen Fan (Water, Air, & Soil Pollution, 2021)

RETRACTED ARTICLE: Assessing the nexus between financial development and energy finance through demand- and supply-oriented physical disruption in crude oil - Fengsheng Chien; YunQian Zhang; Ching-Chi Hsu (Environmental Science and Pollution Research, 2021)

COVID-19 fear and volatility index movements: empirical insights from ASEAN stock markets - Muhammad Sadiq; Ching-Chi Hsu; YunQian Zhang; Fengsheng Chien (Environmental Science and Pollution Research, 2021)

A Comparative Analysis of Slack-Based Green Total Factor Productivity in China: a Directional Distance Function - Xuping Zhang; Xiang Chen; Ching-Cheng Lu; Fu-Yueh Cheng (Water, Air, & Soil Pollution, 2021)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Mass transport release of heavy metal oxyanions from solidified/stabilized co-disposed flue gas desulfurization brine and coal fly ash monoliths - Jay E. Renew; Wenlong Zhang; Ching-Hua Huang (Environmental Science and Pollution Research, 2021)

The novel three-dimensional pulse images analyzed by dynamic L-cube polynomial model - Ching-Hsing Luo; Zhan Zhang; Bo Peng; Xiaohua Xie; Tsung-Lin Lee; Liang-Miin Tsai (Medical & Biological Engineering & Computing, 2021)

Low-pass genome sequencing: a validated method in clinical cytogenetics - Matthew Hoi Kin Chau; Huilin Wang; Yunli Lai; Yanyan Zhang; Fuben Xu; Yanqing Tang; Yanfang Wang; Zihan Chen; Tak Yeung Leung; Jacqueline Pui Wah Chung; Yvonne K. Kwok; Shuk Ching Chong; et al. (Human Genetics, 2020)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Combination of Power Function and Log-Linear Models to Estimate Pile Setup - Murad Y. Abu-Farsakh; Md. Nafiul Haque; Ching Tsai; Zhongjie Zhang (Geotechnical and Geological Engineering, 2018)

Differential expression of hormone related genes between extreme segregants of a Saccharum interspecific F2 population - Fan Zhu; Ching Man Wai; Jisen Zhang; Tyler C. Jones; Chifumi Nagai; Ray Ming (Euphytica, 2018)

Effect of Surfactants on Mechanical, Thermal, and Photostability of a Monoclonal Antibody - Meera Agarkhed; Courtney O’Dell; Ming-Ching Hsieh; Jingming Zhang; Joel Goldstein; Arvind Srivastava (AAPS PharmSciTech, 2018)

Mapping bone marrow niches of disseminated tumor cells - Weijie Zhang; Hin Ching Lo; Xiang H. -F. Zhang (Science China Life Sciences, 2017)

Raman spectra of polycrystalline microdiamond inclusions in zircons, and ultrahigh-pressure metamorphism of a quartzofeldspathic rock from the Erzgebirge terrane, Germany - Ru Y. Zhang; Juhn G. Liou; Ching-Hua Lo (International Geology Review, 2017)

Identification of microRNAs, phasiRNAs and Their Targets in Pineapple - Yun Zheng; Ting Li; Zhenning Xu; Ching Man Wai; Kun Chen; Xiaotuo Zhang; Shengpeng Wang; Bo Ji; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effect of Polysorbate 80 Concentration on Thermal and Photostability of a Monoclonal Antibody - Meera Agarkhed; Courtney O’Dell; Ming-Ching Hsieh; Jingming Zhang; Joel Goldstein; Arvind Srivastava (AAPS PharmSciTech, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

A transposable element insertion within ZmGE2 gene is associated with increase in embryo to endosperm ratio in maize - Pan Zhang; William B. Allen; Nobuhiro Nagasawa; Ada S. Ching; Elmer P. Heppard; Hui Li; Xiaomin Hao; Xiaowei Li; Xiaohong Yang; Jianbing Yan; Yasuo Nagato; Hajime Sakai; et al. (Theoretical and Applied Genetics, 2012)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

Effect of Polysorbate 80 Quality on Photostability of a Monoclonal Antibody - Swita R. Singh; Jingming Zhang; Courtney O’Dell; Ming-Ching Hsieh; Joel Goldstein; Joseph Liu; Arvind Srivastava (AAPS PharmSciTech, 2012)

The integrated WRF/urban modelling system: development, evaluation, and applications to urban environmental problems - Fei Chen; Hiroyuki Kusaka; Robert Bornstein; Jason Ching; C. S. B. Grimmond; Susanne Grossman‐Clarke; Thomas Loridan; Kevin W. Manning; Alberto Martilli; Shiguang Miao; David Sailor; Francisco P. Salamanca; et al. (International Journal of Climatology, 2011)
To bridge the gaps between traditional mesoscale modelling and microscale modelling, the National Center for Atmospheric Research, in collaboration with other agencies and research groups, has developed an integrated urban modelling system coupled to the weather research and forecasting (WRF) model as a community tool to address urban environmental issues. The core of this WRF/urban modelling system consists of the following: (1) three methods with different degrees of freedom to parameterize urban surface processes, ranging from a simple bulk parameterization to a sophisticated multi‐layer urban canopy model with an indoor–outdoor exchange sub‐model that directly interacts with the atmospheric boundary layer, (2) coupling to fine‐scale computational fluid dynamic Reynolds‐averaged Navier–Stokes and Large‐Eddy simulation models for transport and dispersion (T&D) applications, (3) procedures to incorporate high‐resolution urban land use, building morphology, and anthropogenic heating data using the National Urban Database and Access Portal Tool (NUDAPT), and (4) an urbanized high‐resolution land data assimilation system. This paper provides an overview of this modelling system; addresses the daunting challenges of initializing the coupled WRF/urban model and of specifying the potentially vast number of parameters required to execute the WRF/urban model; explores the model sensitivity to these urban parameters; and evaluates the ability of WRF/urban to capture urban heat islands, complex boundary‐layer structures aloft, and urban plume T&D for several major metropolitan regions. Recent applications of this modelling system illustrate its promising utility, as a regional climate‐modelling tool, to investigate impacts of future urbanization on regional meteorological conditions and on air quality under future climate change scenarios. Copyright © 2010 Royal Meteorological Society

Integration of Genetic and Cytological Maps and Development of a Pachytene Chromosome-based Karyotype in Papaya - Wenli Zhang; Ching Man Wai; Ray Ming; Qingyi Yu; Jiming Jiang (Tropical Plant Biology, 2010)

Threatened fishes of the world: Squalidus banarescui Chen and Chang, 2007 (Cyprinidae) - I-Shiung Chen; Nian-Hong Jang-Liaw; Yun-Ching Chang; Villien Weiyun Zhang; Kwang-Tsao Shao (Environmental Biology of Fishes, 2010)

Micro-Electrocardiograms to Study Post-Ventricular Amputation of Zebrafish Heart - Ping Sun; Yolanda Zhang; Fei Yu; Elizabeth Parks; Althea Lyman; Qiong Wu; Lisong Ai; Chang-Hong Hu; Qifa Zhou; Kirk Shung; Ching-Ling Lien; Tzung K. Hsiai (Annals of Biomedical Engineering, 2009)

Contaminant Concentrations and Histopathological Effects in Sacramento Splittail (Pogonichthys macrolepidotus) - Ben K. Greenfield; Swee J. Teh; John R. M. Ross; Jennifer Hunt; GuoHua Zhang; Jay A. Davis; Gary Ichikawa; David Crane; Silas S. O. Hung; DongFang Deng; Foo-Ching Teh; Peter G. Green (Archives of Environmental Contamination and Toxicology, 2008)

Numerical investigation and identification of susceptible sites of atherosclerotic lesion formation in a complete coronary artery bypass model - Jun-Mei Zhang; Leok Poh Chua; Dhanjoo N. Ghista; Simon Ching Man Yu; Yong Seng Tan (Medical & Biological Engineering & Computing, 2008)

Effect of Mycoplasmas on Apoptosis of 32D Cells Is Species-Dependent - Shimin Zhang; Shyh-Ching Lo (Current Microbiology, 2007)

Characterization of an IS Element in Mycoplasma orale That Is Highly Homologous to M. fermentans ISLE - Susan E. Ditty; BingJie Li; Shimin Zhang; Nianxiang Zou; Shyh-Ching Lo (Current Microbiology, 2003)

Effects of Mycoplasmal LAMPs on Receptor Responses to Steroid Hormones in Mammalian Cells - Kaori Iyama; Shimin Zhang; Shyh-Ching Lo (Current Microbiology, 2001)